Dinamika Rekonstruksi Pemaknaan Hidup dari Ibu Tunggal Pasca Perceraian Hidup - Faradhiba Natasya Ho (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
Divorce is a life event that alters the structure of women’s lives and necessitates adjustment to the role of single motherhood. This situation gives rise to emotional burdens, personal changes, various challenges, and the need to reconstruct one’s direction and meaning in life. This study aims to explore the dynamics of meaning reconstruction among single mothers following divorce through an understanding of their subjective experiences. A qualitative approach with a phenomenological method was employed. Data were collected through in-depth semi-structured interviews with three single mothers and analyzed using Moustakas’ stages, namely bracketing, horizonalization, clustering of meanings, textural description, and imaginative variation. The findings indicate that the process of meaning reconstruction is manifested through self-reflection, religiosity, and social support, which contribute to the formation of new meanings in life. This process is characterized by self-acceptance, personal transformation, emotional maturity, and the ability to perceive oneself as an individual possessing agency, value, and life purpose.This study provides theoretical implications by enriching the understanding of meaning reconstruction processes within the context of post-divorce families. Practically, the findings underscore the importance of emotional, spiritual, and social support in psychological interventions aimed at strengthening life meaning and the well-being of single mothers in Indonesia.Â Keywords : Single mothers, Reconstruction of Life Meaning, Divorce